Osteocutaneous radial forearm reconstruction of large partial cricotracheal defects1. Issue 8 (18th September 2012) - Al–Khudari, Samer; Sharma, Saurabh; Young, William; Stapp, Robert; Ghanem, Tamer A.; Chen, Amy; Chen, Amy
Abstract Background Single‐stage procedures for reconstruction of large cricotracheal defects have been limited in success and malignant immature teratomas in the larynx of an adult have never been reported. Methods and Results This was a case report and literature review. A 27‐year‐old man presented with 2 weeks of new‐onset stridor and was found to have a mass obstructing 80% of the subglottis and trachea. He underwent a noncircumferential partial cricotracheal resection with a resultant 7‐cm luminal defect, followed by osteocutaneous radial forearm flap semi‐rigid reconstruction. A novel technique was used to allow a functional and patent airway, which may be applied to other partial luminal reconstructive defects. Postoperatively, the patient was decannulated and has good speech quality and swallowing function. This work was performed at the Henry Ford Health System. This project was reviewed and was granted full approval by the Henry Ford Health System Institutional Review Board. Conclusions This is the first reported case of malignant immature teratoma to involve the larynx, trachea, and recurrent laryngeal nerve in an adult patient, and the first single‐stage technique described to use free tissue transfer without prefabrication for a 7‐cm airway defect. © 2012 Wiley Periodicals, Inc. Head Neck, 2013